2020
DOI: 10.1111/eci.13368
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for adverse outcomes of patients with recanalized chronic total occlusion lesion

Abstract: Background It is ill‐defined which factors affect the prognosis of patients with recanalized chronic total occlusion (CTO). This study sought to investigate predictors for adverse outcome in such a cohort with long‐time follow‐up. Methods From 2010 to 2013, patients with successfully recanalized CTO were included. The primary endpoint was a composite of all‐cause death, myocardial infarction or target vessel revascularization (TVR). The secondary endpoints were TVR and target lesion revascularization (TLR). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Besides, CKD was not routinely evaluated among CTO patients in previous studies. 26 , 33 , 36 In present study, only 51 (7%) patients were with CKD in successful CTO PCI group in our study, and the mean contrast volume was 227mL. Hydration, before and after the CTO procedure, was effective to reduce the occurrence of CIN.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Besides, CKD was not routinely evaluated among CTO patients in previous studies. 26 , 33 , 36 In present study, only 51 (7%) patients were with CKD in successful CTO PCI group in our study, and the mean contrast volume was 227mL. Hydration, before and after the CTO procedure, was effective to reduce the occurrence of CIN.…”
Section: Discussionmentioning
confidence: 50%
“… 31 Furthermore, acute kidney injury (AKI) was an independent prognostic factor for long-term mortality among these patients treated with primary PCI. 32 Interestingly, for CTO patients, age and CKD had no predictive value, 33–35 possibly due to the different study populations. Besides, CKD was not routinely evaluated among CTO patients in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Abe et al argued that J-CTO score can predict the prognosis of patients with CTO [ 12 ]. In a five years follow-up study involving over 2000 patients, J-CTO score and residual SYNTAX score were independently associated to TVR (HR, 1.31; 95% CI: 1.11–1.54; P < 0.01) [ 13 ]. However, a small observational study enrolled only 93 patients identified that reduced TIMI flow of target vessel (OR: 11.0, 95% CI: 2.7–45.5, P = 0.001) as well as female (OR: 11.0, 95% CI: 2.1–58.5, p = 0.005) were the predictors of adverse events, indicating the predictive value of target vessel failure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, powerful evidence is absent when deciding on the revascularization approach in the special CTO population, including multiple CTOs, left ventricular dysfunction or elderly patients. 11,[17][18][19] Hence, more randomized controlled trials regarding these questions are necessary.…”
mentioning
confidence: 99%